2020
DOI: 10.3390/molecules25143234
|View full text |Cite
|
Sign up to set email alerts
|

Aronia melanocarpa Fruits as a Rich Dietary Source of Chlorogenic Acids and Anthocyanins: 1H-NMR, HPLC-DAD, and Chemometric Studies

Abstract: Aronia melanocarpa (Michx.) Elliott’s (chokeberry) besides anthocyanins contains significant amounts of hydroxycinnamic acids: Chlorogenic and its isomer neochlorogenic acid. They exhibit antioxidant, anti-inflammatory, antidiabetic, and antibacterial activities, thus they can have a significant impact on the health-promoting properties of Aronia. The aim of our research was to determine the changes in the content of chlorogenic acids (CGAs) and anthocyanins during fruit development and ripening, with a partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 19 publications
4
27
1
Order By: Relevance
“…The HPLC studies have shown that Cya-3-Gal is responsible for the red color of the leaves. Other pigments pres-ent in chokeberry fruits, mainly cyanidin-3-O-arabinoside [Zielińska et al, 2020], were below detection level in our study. The average content of anthocyanin Cya-3-Gal was found to be 0.52±0.01 mg/g dry weight (d.w.) of red leaves, which was relatively low compared to the fruit (2-3 g/100 g d.w.) [Gralec et al, 2019].…”
Section: Cgas and Anthocyanins In Chokeberry Leaves During Seasonal Gcontrasting
confidence: 82%
See 3 more Smart Citations
“…The HPLC studies have shown that Cya-3-Gal is responsible for the red color of the leaves. Other pigments pres-ent in chokeberry fruits, mainly cyanidin-3-O-arabinoside [Zielińska et al, 2020], were below detection level in our study. The average content of anthocyanin Cya-3-Gal was found to be 0.52±0.01 mg/g dry weight (d.w.) of red leaves, which was relatively low compared to the fruit (2-3 g/100 g d.w.) [Gralec et al, 2019].…”
Section: Cgas and Anthocyanins In Chokeberry Leaves During Seasonal Gcontrasting
confidence: 82%
“…The decrease in CGAs content can be correlated with the appearance of anthocyanins in fruit, which takes place in the middle of July. A similar tendency was observed dur- ing the analysis of chokeberry fruit extracts during ripening [Zielińska et al, 2020]. In green fruit, the content of CGAs was remarkably high, then it decreased and remained unchanged till the end of the season (October).…”
Section: Cgas and Anthocyanins In Chokeberry Leaves During Seasonal Gsupporting
confidence: 79%
See 2 more Smart Citations
“…In addition, structurally diverse compounds were isolated including the lignan (−) hinokinin (14) [21], the xanthone oliganthin K (15) [22], the flavonoids hyperoside (16) [23], avicularin (17) [24] and quercetin 3-O-(2-O-acetyl)-arabinofuranoside (18) [24] (▶ Fig. 1), chlorogenic acid (19) and neochlorogenic acid (20) [25], (−)-epicatechin (21) [26], β-amyrin (22) [27], lupeol (23) [28], and protocatechuic acid (24) [29]. The isolated PAPs were evaluated for their anti-inflammatory effects in vitro for the reduction of the ICAM-1 expression induced by TNF-α in the HMEC-1 cell line.…”
Section: Introductionmentioning
confidence: 99%